Manajemen Pendidikan Anak Usia Dini (PAUD) dalam Rangka Meningkatkan Mutu Pembelajaran: Studi pada PAUD Daarul Hikmah dan PAUD Al Ikhlas Kabupaten Bogor - Siti Aminah; Ade Ahmad Mubarok; Achmad Mudrikah; Ujang Cepi Barlian (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
This study aims to: analyze the comparison of curriculum management, student management and financial management in improving the quality of learning between PAUD Daarul Hikmah and PAUD Al Ikhlas. The research method uses a descriptive analysis of the comparison between the two institutions by looking at the differences and similarities in managing early childhood education institutions. As a result, PAUD curriculum management has been carried out by both institutions to improve the quality of early childhood education learning, namely the services provided in the kindergarten group (TK) and the game group (KB). The students were happy to be able to go to PAUD Daarul Hikmah and PAUD Al Ikhlas. Service provision has met student service standards and agreements with the needs of the surrounding community. Student management in both PAUD has met the standard of achieving children's development, the PAUD head has planned very well, learning is carried out according to age groups, and also according to the needs of the surrounding community and the students themselves. Financial management in PAUD Daarul Hikmah and PAUD Al Ikhlas is in accordance with the instructions and rules regarding the finances of PAUD implementation. Both financial management has also been communicated with parents, students, and the community so that there is no rejection from the community. Keywords: Curriculum Management, Student Management, Financial Management, PAUD